Politics and power - Kidd, Warren; Legge, Karen; Harari, Philippe (New York : Palgrave Macmillan, 2010)
"Politics and Power offers a lively and up-to-date overview of classic and contemporary debates in an important sub-area of the discipline. As with other titles in the series, it provides both a careful blend of theory, evidence and examples and a stimulating array of exercises and activities for the student to apply and reinforce their understanding. Covering issues and debates ranging from theories of power, the state and nationalism to voting patterns, political ideologies, and the role of direct action in political processes, it is an ideal starting-point for any student wishing to gain a strong basic grounding in political sociology"--Provided by publisher.
Introducing the nature of power and politics in everyday life -- Classical views on power and politics -- Theories on the nature and distribution of power -- A new sociology of politics for a new world? -- Changing ideologies and the transformation of political parties in the UK -- Understanding individual political participation -- Theories on the role of the state in society -- Globalization, nationalism and revolution.
Includes bibliographical references and index.
Keywords: Power (Social sciences); Political sociology